Cardiac Emergency Preparedness in Health/Fitness Facilities in Australia. Issue 4 (November 2014) - Sekendiz, Betul; Gass, Gregory; Norton, Kevin; Finch, Caroline F.
Abstract: Background: Health/fitness facilities are popular venues for physical activity, where increasingly more individuals at risk of cardiovascular events exercise to achieve positive health outcomes. The aim of our study was to analyze cardiac emergency preparedness in health/fitness facilities in Queensland, Australia.Design: Cross-sectional survey of health/fitness facilities in Queensland.Methods: A risk management questionnaire was administered over 7 months, July 2009 to January 2010, using an online or paper-based version. The data are presented as the proportion of survey respondents giving specific responses to questionnaire items related to cardiac emergency preparedness, especially the provision of automated external defibrillators (AEDs).Results: Fifty-two health/fitness facility managers responded to the survey. Most of the surveyed facilities conducted pre-activity screening (92%). Of those with a written emergency plan (79%), only 37% physically rehearsed their emergency response systems at regular intervals. Ninety-five percent of the facilities had fitness employees with a current first aid/cardiopulmonary resuscitation certificate and training. Of the 10 (19%) facilities with an on-site AED, only 6 had staff qualified to use the AED in an emergency, and only 6 had the AED as part of a public access defibrillator program.Conclusion: This is the first study to report that cardiac emergency preparedness is not optimal in the health/fitness facilities in Australia. Development of policies and procedures for training health/fitness professionals in emergency procedures is needed to minimize the risk when exercise-induced cardiac events occur at health/fitness facilities.